Electrochemical Properties and Sodium‐Storage Mechanism of Ag2Mo2O7 as the Anode Material for Sodium‐Ion Batteries. Issue 21 (9th April 2016) - Chen, Nan; Gao, Yu; Zhang, Meina; Meng, Xing; Wang, Chunzhong; Wei, Yingjin; Du, Fei; Chen, Gang
Abstract: Silver molybdate, Ag2 Mo2 O7, has been prepared by a conventional solid‐state reaction. Its electrochemical properties as an anode material for sodium‐ion batteries (SIBs) have been comprehensively examined by means of galvanostatic charge–discharge cycling, cyclic voltammetry, and rate performance measurements. At operating voltages between 3.0 and 0.01 V, the electrode delivered a reversible capacity of nearly 190 mA h g −1 at a current density of 20 mA g −1 after 70 cycles. Ag2 Mo2 O7 also demonstrated a good rate capability and long‐term cycle stability, the capacity reaching almost 100 mA h g −1 at a current density of 500 mA g −1, with a capacity retention of 55 % over 1000 cycles. Moreover, the sodium storage process of Ag2 Mo2 O7 has been investigated by means of ex situ XRD, Raman spectroscopy, and HRTEM. Interestingly, the anode decomposes into Ag metal and Na2 MoO4 during the initial discharge process, and then Na + ions are considered to be inserted into/extracted from the Na2 MoO4 lattice in the subsequent cycles governed by an intercalation/deintercalation mechanism. Ex situ HRTEM images revealed that Ag metal not only remains unchanged during the sodiation/desodiation processes, but is well dispersed throughout the amorphous matrix, thereby greatly improving the electronic conductivity of the working electrode. The "in situ" decomposition behavior of Ag2 Mo2 O7 is distinct from that of chemically synthesized, metal‐nanoparticle‐coated electrode materials, and provides strong supplementary insight into the mechanism of such new anode materials for SIBs and may set a precedent for the design of further materials. Abstract : Anode for sodium‐ion batteries : Ag2 Mo2 O7 has been investigated as an anode material for sodium‐ion batteries. It delivered a high reversible capacity of nearly 190 mA h g −1 and long‐term cycle life with a capacity retention of 55 % over 1000 cycles at a current density of 500 mA g −1 . The phase evolution of the Ag2 Mo2 O7 electrode has been examined by ex situ XRD, Raman spectroscopy, and HRTEM analyses (background in figure).